Application of a high density adsorbent in expanded bed adsorption of lipase from Burkholderia pseudomallei - Yong, Hor Shee; Tey, Beng Ti; Hii, Siew Ling; Mustapa Kamal, Siti Mazlina; Ariff, Arbakariya; Ling, Tau Chuan (Academic Journals, 2010)
The application of STREAMLINE Direct HST adsorbent in expanded bed adsorption of lipase from Burkholderia pseudomallei was explored in this study. Scouting of optimum binding and elution condition was performed in batch binding mode. Theaddition of 0.2 M salt in acetate buffer (pH 5) during adsorption has increased thespecificity and quantity of lipase binding onto the adsorbent. The addition of 0.4 M salt in phosphate buffer (pH 7) achieved the highest purification fold (2.5) in elution. The high density of the adsorbent allowed the EBA to be operated at linear velocityas high as 657 cm/h with feedstock containing 4.5% (w/v) wet biomass. The Richardson-Zaki correlation obtained for this EBA system at the presence of 4.5% (w/v) wet biomass is 5.14, a value closed to the laminar flow regime of 4.8, demonstrated that a stable bed is achieved under this operating condition.Meanwhile, a flow velocity of 343 cm/h with bed expansion of 3.2 gave highest dynamic binding capacity (4979.28 U/ml) and productivity (61.52 U/ml.min) for this EBA operation. It also demonstrated that biomass concentration up to 4.5% (w/v) wet weight showed slightly drop of sorption efficiency (0.82) compared to lower biomass concentration (0.94). Further increase of biomass concentration above 4.5% (w/v) wet weight has greatly decreased the equilibrium and dynamic capacity. Application of high density adsorbent tolerated to high density and biomass has reduced the processing time and increased the productivity.